(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Visual dysfunction is frequent in multiple sclerosis, usually resulting from retrobulbar optic neuritis or papillitis. Less frequently, demyelinating lesions can affect the retrochiasmal pathways. There are few reports of homonymous visual field defects (HVFD) in multiple sclerosis and little is known about their evolution. The purpose of this study was to better define both the clinical profile and the evolution of HVFD in patients with multiple sclerosis. METHODS We performed a retrospective study of all multiple sclerosis patients who presented HVFD and were examined by automated static perimetry. A subset of patients benefited from macular assessment with optical coherence tomography (OCT). We also reviewed the worldwide literature on the subject. RESULTS Twenty patients were retrieved from the neuro-ophthalmology database of the Hôpital Ophtalmique Jules-Gonin. There were 11 women and 9 men, and their average age was 35 ± 11 years. The relapsing-remitting form of multiple sclerosis was most common (18/20; 90%), the primary progressive form (1/20; 5%) and the secondary progressive form (1/20; 5%) were rare. HVFD were the presenting symptom of multiple sclerosis in seven patients (35%). The recovery was complete in 12/20 patients (60%), and the median time to recovery was 10 weeks (2-13 weeks). An incomplete recovery was found in 5/20 subjects (25%) and no recovery occurred in 3/20 subjects (15%). Magnetic resonance imaging disclosed a definite lesion explaining the HVFD in 7/11 patients: five within the optic radiations (71.4%), one within the optic tract (14.3%) and one within the lateral geniculate nucleus (14.3%). Our results were comparable to those compiled from our literature search (29 publications, totalling 70 cases). A recurrent episode of HVFD occurred in three patients (15%). OCT was performed in 10/20 patients. Retinal ganglion cell layer thickness was assessed and revealed a homonymous thinning in three patients, diffuse unilateral or bilateral thinning (resulting from previous episodes of optic neuritis) in six patients, and normal retinal ganglion cell layer thickness in one patient. CONCLUSION HVFD in multiple sclerosis are found mostly in young patients with relapsing-remitting multiple sclerosis, which is consistent with the epidemiology of multiple sclerosis. HVFD can be the first manifestation of multiple sclerosis and have a relatively good prognosis. Like optic neuritis, HVFD can recur. The incidence of HVFD in multiple sclerosis is unknown, as it is probably underdiagnosed. Systematic automated static perimetry and OCT could help to determine the true incidence of HVFD in multiple sclerosis.